Feedlot performance of nine hybrid sorghum grains fed to steers winter, 1971-1972 - R.L. McCollough; Jack G. Riley; C.L. Drake; G.M. Roth (Kansas Agricultural Experiment Station Research Reports, 1972)
Previous trials here indicated a possible difference in nutritional values of different hybrid sorghum grains with yellow endosperm hybrids being superior to white endosperm. We compared feedlot performance of yellow endosperm, white endosperm, all waxy (amylopectin type starch), and part waxy hybrid sorghum grains.
Keywords: Cattlemen' s Day; 1972; Report of progress (Kansas State University. Agricultural Experiment Station); 557; Beef; Feedlot performance; Hybrid sorghum; Steers